2018
DOI: 10.1186/s12891-018-2037-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between low back pain and professional driving in young military recruits

Abstract: BackgroundEpisodes of low back pain (LBP) are very common among workers. A number of occupational risk factors have been shown to increase the risk for LBP. One of these risk factors is exposure to whole body vibration, which is a known characteristic in driving professions. The aim of this study was to assess the impact of driving on LBP amongst young professional drivers.MethodsThis is an historical-prospective cohort study based on the Israel Defense Forces (IDF) database of male soldiers drafted between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…A total of 11,346 studies appeared in the searches and 49 were included in this systematic review (Figure ) with over 125,000 study participants followed‐up. Ten studies (Harkness, Macfarlane, Nahit, Silman, & McBeth, ; Mikkonen et al, , , , ; Mitchell et al, ; Nemoto et al, , ; Power, Frank, Hertzman, Schierhout, & Li, ; Smith, Russell, & Hodges, ) reported risk factors for first episode of back pain, two reported risk factors for a new episode (Mostardi, Noe, Kovacik, & Porterfield, ; Videman, Ojajarvi, Riihimaki, & Troup, ) and 30 reported risk factors for a mixture of participants with first episode and a new episode of back pain (Adams, Mannion, & Dolan, ; Auvinen et al, ; Baranto, Hellstrom, Cederlund, Nyman, & Sward, ; Cholewicki et al, ; Claeys et al, ; Coenen et al, ; Feyer et al, ; Greene, Cholewicki, Galloway, Nguyen, & Radebold, ; Hestbaek, Korsholm, Leboeuf‐Yde, & Kyvik, ; Hestbaek Leboeuf‐Yde, & Kyvik, , ; Hestbaek, Leboeuf‐Yde, Kyvik, & Manniche, ; Kanchanomai, Janwantanakul, Pensri, & Jiamjarasrangsi, ; Kato et al, ; Kroner‐Herwig, Gorbunova, & Maas, ; Lake, Power, & Cole, ; Lallukka et al, ; Lunde, Koch, Hanvold, Waersted, & Veiersted, ; Lundin, Hellstrom, Nilsson, & Sward, ; Mannion, Dolan, & Adams, ; Monnier, Djupsjöbacka, Larsson, Norman, & Äng, ; Nadler, Wu, Galski, & Feinberg, ; Ogon et al, ; Poussa et al, ; Roy & Lopez, ; Salminen, Erkintalo, Laine, & Pentti, ; Salminen, Erkintalo, Pentti, Oksanen, & Kormano, ; Silfies, Cholewicki, Reeves, & Greene, ; Van Nieuwenhuyse et al, ; Zack, Levin, Krakov, Finestone, & Moshe, ). Seven studies did not report the status of new or first episode of back pain (Brady et al, ; Cheung, ; Hayes, Smith, & Taylor, ; Hertzberg, ; Klaber Moffett, Hughes, & Griffiths, ; Lee et al, ; Rosenhagen, Nieder...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 11,346 studies appeared in the searches and 49 were included in this systematic review (Figure ) with over 125,000 study participants followed‐up. Ten studies (Harkness, Macfarlane, Nahit, Silman, & McBeth, ; Mikkonen et al, , , , ; Mitchell et al, ; Nemoto et al, , ; Power, Frank, Hertzman, Schierhout, & Li, ; Smith, Russell, & Hodges, ) reported risk factors for first episode of back pain, two reported risk factors for a new episode (Mostardi, Noe, Kovacik, & Porterfield, ; Videman, Ojajarvi, Riihimaki, & Troup, ) and 30 reported risk factors for a mixture of participants with first episode and a new episode of back pain (Adams, Mannion, & Dolan, ; Auvinen et al, ; Baranto, Hellstrom, Cederlund, Nyman, & Sward, ; Cholewicki et al, ; Claeys et al, ; Coenen et al, ; Feyer et al, ; Greene, Cholewicki, Galloway, Nguyen, & Radebold, ; Hestbaek, Korsholm, Leboeuf‐Yde, & Kyvik, ; Hestbaek Leboeuf‐Yde, & Kyvik, , ; Hestbaek, Leboeuf‐Yde, Kyvik, & Manniche, ; Kanchanomai, Janwantanakul, Pensri, & Jiamjarasrangsi, ; Kato et al, ; Kroner‐Herwig, Gorbunova, & Maas, ; Lake, Power, & Cole, ; Lallukka et al, ; Lunde, Koch, Hanvold, Waersted, & Veiersted, ; Lundin, Hellstrom, Nilsson, & Sward, ; Mannion, Dolan, & Adams, ; Monnier, Djupsjöbacka, Larsson, Norman, & Äng, ; Nadler, Wu, Galski, & Feinberg, ; Ogon et al, ; Poussa et al, ; Roy & Lopez, ; Salminen, Erkintalo, Laine, & Pentti, ; Salminen, Erkintalo, Pentti, Oksanen, & Kormano, ; Silfies, Cholewicki, Reeves, & Greene, ; Van Nieuwenhuyse et al, ; Zack, Levin, Krakov, Finestone, & Moshe, ). Seven studies did not report the status of new or first episode of back pain (Brady et al, ; Cheung, ; Hayes, Smith, & Taylor, ; Hertzberg, ; Klaber Moffett, Hughes, & Griffiths, ; Lee et al, ; Rosenhagen, Nieder...…”
Section: Resultsmentioning
confidence: 99%
“…The population sources included health care workers ( n = 4 studies; Adams et al, ; Mannion et al, ; Mostardi et al, ; Van Nieuwenhuyse et al, ), athletes or university students ( n = 18; Baranto et al, ; Cheung, ; Cholewicki et al, ; Claeys et al, ; Feyer et al, ; Greene et al, ; Hayes et al, ; Kanchanomai et al, ; Kato et al, ; Klaber Moffett et al, ; Lee et al, ; Lunde et al, ; Lundin et al, ; Mitchell et al, ; Nadler et al, ; Rosenhagen et al, ; Silfies et al, ; Videman et al, ) and population cohorts ( n = 15), such as the British and Northern Finland Birth Cohorts (Auvinen et al, ; Brady et al, ; Coenen et al, ; Hestbaek et al, , ; Hestbaek, Leboeuf‐Yde, & Kyvik, ; Hestbaek et al, ; Lake et al, ; Lallukka et al, ; Mikkonen et al, , , , ; Power et al, ; Smith et al, ). Five studies included participants from government‐funded schools (Hertzberg, ; Ogon et al, ; Poussa et al, ; Salminen et al, , ), and five studies included soldiers or military personnel (Monnier et al, ; Nemoto et al, , ; Roy & Lopez, ; Zack et al, ; Table ). One study investigated participants from different work sites (Harkness et al, ), and another used a prospective cohort from a paediatric pain study (Kroner‐Herwig et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations